Plasmonic enhancement of electroluminescence - Demir, Hilmi Volkan (2018)
Here plasmonic effect specifically on electroluminescence (EL) is studied in terms of radiative and nonradiative decay rates for a dipole near a metal spherical nanoparticle (NP). Contribution from scattering is taken into account and is shown to play a decisive role in EL enhancement owing to pronounced size-dependent radiative decay enhancement and weak size effect on non-radiative counterpart. Unlike photoluminescence where local incident field factor mainly determines the enhancement possibility and level, EL enhancement is only possible by means of quantum yield rise, EL enhancement being feasible only for an intrinsic quantum yield Q0 < 1. The resulting plasmonic effect is independent of intrinsic emitter lifetime but is exclusively defined by the value of Q0, emission spectrum, NP diameter and emitter-metal spacing. For 0.1< Q0 < 0.25, Ag nanoparticles are shown to enhance LED/OLED intensity by several times over the whole visible whereas Au particles feature lower effect within the red-orange range only. Independently of positive effect on quantum yield, metal nanoparticles embedded in an electroluminescent device will improve its efficiency at high currents owing to enhanced overall recombination rate which will diminish manifestation of Auger processes. The latter are believed to be responsible for the known undesirable efficiency droop in semiconductor commercial quantum well based LEDs at higher current. For the same reason plasmonics can diminish quantum dot photodegradation from Auger process induced non-radiative recombination and photoionization thus opening a way to avoid negative Auger effects in emerging colloidal semiconductor LEDs.